hiding data in a text using color variance - Sundus Khalil Ibrahim; Warkaa Mohammad Hisham Yousif (مجلة التربية والعلم, 2013)
Abstract: Hiding secret information and data in a cover such as audio, image, or video files makes the files unsuspicion for the an reader. So, this is the main reason for this research in the steganography field, comparing with encryption methods. The encrypt text pay the tracker to use various methods to break the encryption and get the original text. While the steganography draw no attention, and the reader may pass over it without doubt thus, the file and the hiding data stay without damage. This paper presents a new method for hiding data in a text using color variance. In the recovery step, the text file of the covered message converted to digital image form, and image processing methods used to extract the hiding data from it. The proposed method applied on Arabic and English texts. Most types of attacking are applied in the messages. It shows a high efficiency versus all applied types of attacking. Matlab 2010a is used in programming the proposed method.